Compressive strength and specific strength of porous nickel foam/resin composite material - LIU Peisheng; CHENG Yuyang; CHENG Wei; CHEN Bin; LI Xiangyu (Cailiao gongcheng)
The nickel foam （the average pore diameter is about 2.7 mm，and the porosity is 93.1%） is used for the epoxy resin to coat the pore-struts， and the porous nickel foam/epoxy resin composite is obtained with such pore-struts as a multi-layer structure. The compression performance experiments are conducted on the obtained composite samples， and the mechanical strength is emphatically analyzed. The results show that the compressive strength and the specific strength of the composite samples are both significantly higher than those of the original nickel foam， respectively. When the nickel foam （with a bulk density of about 0.6 g·cm-3） is coated to make nickel foam/resin composite samples （with a bulk density of about 0.72-0.82 g·cm-3）， the compressive strength increases from 0.75 MPa to 2.24-2.68 MPa， and the specific strength increases from 1.23 MPa·cm3·g-1 to 3.09-3.27 MPa·cm3·g-1. The relationship between compressive strength and porosity of composite samples conforms to the corresponding mathematical relationship based on the octahedral model theory. According to the relevant mechanical model， the overall failure of the composite samples is caused by the priority failure of the pore-strut core.